ANALISIS TINGKAT BAHAYA EROSI PADA SUB DAS AIR LEMATANG KOTA PAGAR ALAM - Fanisa Dzaliqia azani; Barrorotul Azizah (JURNAL ILMIAH BERING'S, 2019)
The Lematang Water Basin Sub Watershed is a upstream basin located in Pagar Alam City, South Sumatra. From BPS data (Central Bureau of Statistics) in 2016 the area of ​​Air Lematang sub watershed is 37,500 ha. According to SK Menhut No 866, the total area of ​​protected forest in Pagar Alam city is 26,065 ha and that has been damaged according to data from SLHD (Environmental Status of the Region) is 3,622.65 ha. From the above data the land cover conditions that occur in the sub watershed Water Lematang has experienced degradation of land where the protected forest area has become settlement and agricultural land, so potentially to the erosion of land in the area. The objective of this research is to analyze soil erosion in sub watershed of Lematang Water and to identify the level of erosion hazard in Water Lematang sub watershed. Analysis of Erosion Hazard (TBE) data was performed using the Universal Soil Loss Equation (USLE) formula and approached using the GIS application. The result of the analysis shows the area of ​​land with very light erosion level of 42,335 ha, light 55,150 ha, medium 70,552 ha, weight 22,268 ha, very heavy 30,882 ha. The level of erosion hazard that occurs in the sub watershed Water Lematang included into the medium category has not been too heavy, the action should be taken to maintain and preserve the sub watershed Air Lematang still done because it would be better to continue to do good soil farming so as not to be a serious erosion hazard level